Synergistic action of olive oil supplementation and dietary restriction on serum lipids and cardiac antioxidant defences - Faine, Luciane A. [UNESP]; Diniz, Yeda S. [UNESP]; Galhardi, Cristiano M. [UNESP]; Rodrigues, Hosana G.; Burneiko, Regina C. [UNESP]; Santana, Lea S. [UNESP]; Cicogna, Antonio Carlos [UNESP]; Novelli, Ethel L.B. (Canadian Science Publishing, 2004)
Caloric intake is higher than recommended in many populations. Therefore, enhancing olive oil intake alone may not be the most effective way to prevent cardiovascular diseases. The purpose of the present study was to analyse the association of olive oil and dietary restriction on lipid profile and myocardial antioxidant defences. Male Wistar rats (180-200 g, n = 6) were divided into 4 groups: control ad libitum diet (C), 50% restricted diet (DR), fed ad libitum and supplemented with olive oil (3 mL/(kg-day)) (OO), and 50% restricted diet and supplemented with olive oil (DROO). After 30 days of treatments, OO, DR, and DROO groups had increased total cholesterol and high-density lipoprotein cholesterol concentrations. DR and DROO animals showed decreased low-density lipoprotein cholesterol. DROO had the lowest low-density lipoprotein cholesterol concentration. Total lipids and triacylglycerols were raised by dietary restriction and diminished by olive oil. OO rats had higher myocardial Superoxide dismutase and lower catalase and glutathione peroxidase activities than C rats. DR and DROO showed enhanced cardiac Superoxide dismutase, catalase, and glutathione peroxidase activities from the control. Olive oil supplementation alone improved the lipid profile but was more effective when coupled with dietary restriction. There was a synergistic beneficial action of dietary restriction and olive oil on serum lipids and myocardial antioxidant defences.
Keywords: Antioxidant enzymes; Cardiac tissue; Dietary restriction; Lipid profile; Olive oil; antioxidant; catalase; cholesterol; glutathione peroxidase; high density lipoprotein cholesterol; lipid; low density lipoprotein cholesterol; olive oil; superoxide dismutase; triacylglycerol; animal experiment; animal tissue; antioxidant activity; caloric intake; controlled study; diet restriction; diet supplementation; enzyme activity; fat intake; glutathione metabolism; heart left ventricle; heart muscle metabolism; male; nonhuman; priority journal; rat; Animals; Antioxidants; Caloric Restriction; Cholesterol; Dietary Supplements; Male; Myocardium; Plant Oils; Rats; Rats, Wistar